Pengaruh Komunikasi Digital, Kepuasan Mahasiswa, Inovasi, Kolaborasi Digital Terhadap Reputasi Organisasi di Universitas Mbojo Bima - Anhikmah, Anhikmah; Priyo Sadono , Teguh; Hamim, Hamim (CV RIFAINSTITUT, 2025)
This study aims to analyze the influence of digital communication, student satisfaction, innovation, and digital collaboration on organizational reputation at Mbojo University of Bima. Using an explanatory quantitative approach, this research involved 251 respondents selected through purposive sampling techniques. Data were collected using a questionnaire that has been tested for validity and reliability. The results of the regression analysis indicate that all independent variables have a positive and significant effect on organizational reputation. Among these variables, student satisfaction has the greatest impact, followed by digital collaboration, innovation, and digital communication. This study underscores the importance of effective and responsive communication, as well as innovation in teaching methods, to enhance the university's reputation. The findings provide insights for university management in designing strategies that can strengthen organizational reputation in the eyes of students and other stakeholders. Practical and academic recommendations are also presented to support further development in this field of research.